The Role of Digital Platforms and Online User Interaction in Shaping Tourist Emotional Satisfaction - Qori Fauziah; Asmar Yulastri; Yudha Aditya Fiandra; Dony Novaliendry (Jurnal Teknologi Informasi dan Pendidikan, 2026)
Tourist experiences in the digital era are shaped not only by on-site physical interactions but are increasingly influenced by digital platforms, online reviews, and social media. Although the literature on digital tourism is growing rapidly, a gap remains in understanding how digital interactions holistically and integratively influence tourists' emotional satisfaction, particularly in coastal destinations. This study aims to examine the role of digital and information technology-based factors in shaping tourists' emotional satisfaction in coastal destinations by developing an integrated model that links the physical and social environments, digital experience quality, electronic word of mouth (e-WOM), digital destination image, and tourist engagement. Data were collected from 339 tourists who actively used digital platforms during their visits to a coastal destination in Indonesia. A mixed-method analytical approach was employed, combining Partial Least Squares Structural Equation Modeling (PLS-SEM) to test linear relationships and fuzzy-set Qualitative Comparative Analysis (fsQCA) to uncover complex configurational pathways leading to high emotional satisfaction. The findings indicate that digital experience quality and e-WOM significantly strengthen digital destination image, which in turn enhances tourist engagement and emotional satisfaction. Tourist engagement emerged as the strongest direct predictor of emotional satisfaction. The configurational analysis revealed multiple alternative pathways leading to high satisfaction, with digital destination image identified as a necessary condition across all configurations. This study offers theoretical contributions by integrating environmental psychology and digital tourism literature into a comprehensive model and by applying a mixed-method approach (SEM-fsQCA) capable of capturing causal complexity. Practically, the findings underscore the importance for destination managers to not only manage physical attractions but also to proactively build a strong digital destination image, encourage positive e-WOM, and create interactive and engaging digital experiences to enhance tourists' emotional satisfaction.